Towards Enhancing Parental Engagement in Their Children Early Learning Opportunities: Does Asset-Based Approach Matter in Tanzanian Pre-Primary Education? - Kojo, Johnson; Seni, Jacob; Ndibalema, Placidius (Universitas Majalengka, 2025)
The purpose of this study was to explore how asset-based approach (ABA) can be used to enhance parental engagement in Tanzanian pre-primary schools. The study was qualitative in nature in which phenomenographical design was adopted. It consisted of six focus group sessions with a total 34 parents. Individual interviews with five pre-primary school teachers, four head teachers and five chair persons of the school committees was conducted in the six selected schools in Nzega district, Tabora region, Tanzania. Transcripts were thematically analysed using simultaneous inductive open coding and deductive coding using TCABA framework as an illustrative lens. The results revealed that the shift towards asset-based approach was felt to offer better opportunities in enhancing parental engagement in children’s early learning. However, a significant number participants were unable to provide specific examples of the assets that parents were possessing which could be utilised to support children’s learning in pre-primary schools. The results further showed that using asset-based approach was affected or enabled by different factors, which included community perspectives, lack of time time/resources and awareness. The results support the need for intervention programmes that empower parents to effectively utilise their skills, knowledge, and talents that are essential for supporting their children’s learning at home and in pre-primary schools.